Enhancing Exposition Text Learning with Construct 2-Based Mind Mapping Media for Elementary Students - Indah Luthfia Khoirunnisa; Sri Sukasih (STAI Hubbulwathan Duri, 2025)
This study investigates the development and effectiveness of Construct 2-based Mind Mapping media in enhancing fifth-grade students’ reading comprehension and learning outcomes on exposition text material. The research followed a Research and Development (RD) approach using the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation phases. A mixed methods design was applied to explore both the development process and its impact on learning. Participants included fifth-grade students from SDN 1 Kalikebo, Klaten. Data were collected through observations, interviews, questionnaires, and reading comprehension tests. The data analysis involved descriptive statistics, paired sample t-tests with normality prerequisite testing, and n-gain calculations to measure learning improvements. The findings indicate that the Construct 2-based Mind Mapping media significantly improved students’ reading comprehension and learning outcomes. The interactive and accessible design of the media made it engaging and aligned with students' learning needs. This supports existing theories emphasizing the benefits of visual learning tools in enhancing comprehension. The results also highlight the media’s relevance and appeal, suggesting that it can be a practical aid for both teachers and students in classroom settings. The study concludes that innovative, interactive learning media can play a critical role in improving academic outcomes. It encourages educators to adopt such media to enrich their teaching strategies and better support students’ learning experiences.